2020
DOI: 10.1186/s40249-020-00699-y
|View full text |Cite
|
Sign up to set email alerts
|

Soluble IL-2Rα correlates with imbalances of Th1/Th2 and Tc1/Tc2 cells in patients with acute brucellosis

Abstract: Background Previous studies showed that soluble IL-2Rα is an important marker of cellular immune activation and might be a marker of treatment efficacy for children with brucellosis. However, data regarding adult patients with brucellosis were unknown. The aim of study was to explore the potential role of serum sIL-2Rα evaluating treatment responses in adult patients with brucellosis, and T cell immune status was also examined. Methods During January 2016–April 2017, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This means Tc1 may trigger IFN-γ primed macrophage populations to secrete pro-inflammatory cytokines such as IL-1β, which promotes aggravating intrauterine inflammation and contributes to placental dysfunction. One recent study suggested that the clearance of Brucella requires IFN-γ-mediated type-1 T cell (Th1/Tc1) immune responses ( 38 , 39 ), while the IL-4, IL-10, Th2/Tc2 response determines susceptibility to Brucella and disease severity ( 40 , 41 ). In another study, in vitro -generated tumor-reactive Tc2 cells were less efficient in eliminating lung tumors than Tc1 cells ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means Tc1 may trigger IFN-γ primed macrophage populations to secrete pro-inflammatory cytokines such as IL-1β, which promotes aggravating intrauterine inflammation and contributes to placental dysfunction. One recent study suggested that the clearance of Brucella requires IFN-γ-mediated type-1 T cell (Th1/Tc1) immune responses ( 38 , 39 ), while the IL-4, IL-10, Th2/Tc2 response determines susceptibility to Brucella and disease severity ( 40 , 41 ). In another study, in vitro -generated tumor-reactive Tc2 cells were less efficient in eliminating lung tumors than Tc1 cells ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance between the production of Tc1 and Tc2 cytokines contributes to an impairment in T cell-mediated immunity, which may ultimately impact anti-bacterial immune responses ( 41 ). In this study, we observed a loss of homeostasis between placental Tc1, Tc2, and their cytokine production following LPS intrauterine administration.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 16 , 18 This result may support our previous study results indicating elevated percentages of Th1 and Th2 cells in patients with acute brucellosis. 17 Th17 cells are induced by IL-6, IL-21, and TGF-β, and IL-17A is the major effector molecule of Th17 cells. 24 IL-17A is a pro-inflammatory cytokine that promotes the protective immune response against bacterial infections but mediates tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In human brucellosis, increasing evidence suggests that infection induced by Brucella disrupts cytokine expression and function of the CD4 + Th and CD8 + cytotoxic T cells and that infection progression is mainly associated with Th2 cytokines. 16,17 In particular, TNF-α, IFN-γ, IL-2, and IL-10 levels are affected during Brucella infection. 16,18,19 Additionally, the level of these cytokine indicates the status of the immune response and disease progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation